ANALYSIS OF TRANSPORTATION METHODS IN MANAGING THE DISTRIBUTION OF SOLO ICE TEA IN SOUTH TANGERANG - Rani,; Ratih Setyo Rini,; Ayu Azizah,; Khoirul ulum, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The contemporary beverage industry in Indonesia is growing rapidly along with the increasing public interest in fresh and practical products, one of which is Es Teh Solo. In the product distribution process, transportation cost efficiency is an important factor to maintain competitiveness and business sustainability. This study aims to analyze the application of transportation methods as part of operations research in optimizing the distribution costs of Es Teh Solo from the factory in South Tangerang to three destination areas, namely South Jakarta, Bogor, and Depok. The methods used include North West Corner (NWC), Least Cost (LC), Vogel's Approximation Method (VAM), and Stepping Stone (SS). The results show that the NWC, VAM, and Stepping Stone methods produce the same minimum cost, which is Rp 8,650,000, while the Least Cost method produces a higher cost, which is Rp 13,020,000. The Stepping Stone method is used to test the optimality of the solution and proves that the value of Rp 8,650,000 is the optimal solution for the Es Teh Solo distribution system. Thus, the application of transportation methods is proven to be effective in minimizing distribution costs and assisting efficient logistics decision making for the company.